Proceedings of the International Conference on Culture and Language in Southeast Asia (ICCLAS 2017) 2018
DOI: 10.2991/icclas-17.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

The Islamic Terms Translation in Kalimatun Sawa’ an Indonesian Bulletin

Abstract: --This research study aims to find out how the Islamic terms on the source text (ST) dealing to the target text (TT) -English language-with same sense and meaning. It is analyzed qualitatively by using some translation strategies considered as linguistic approach and semantic approach. The data were obtained from Islamic terms taken randomly from a bilingual bulletin existed in Indonesia. From linguistics side, it found 3 data of borrowing, 1 data of transposition, and adaptation is 0 data. Meanwhile, from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Additionally, differences in cultures, structures and linguistic forms of both languages are named as the problems (Abdellah, 2002;Daoud Khammyseh, 2015). In another study that focuses on the translation of Islamic terms from Indonesian language (source) to the English language (target) of an Indonesian language bulletin, the researcher found that the main cause of inaccurate translation is when the translator focuses on the words instead of the meaning intended in the source language (Suriadi, 2018). This is in line with another research that suggests the importance of content/meaning and also form/structure when translating religious texts (Butnariu, 2017).…”
Section: Translation and Da'wahsupporting
confidence: 65%
“…Additionally, differences in cultures, structures and linguistic forms of both languages are named as the problems (Abdellah, 2002;Daoud Khammyseh, 2015). In another study that focuses on the translation of Islamic terms from Indonesian language (source) to the English language (target) of an Indonesian language bulletin, the researcher found that the main cause of inaccurate translation is when the translator focuses on the words instead of the meaning intended in the source language (Suriadi, 2018). This is in line with another research that suggests the importance of content/meaning and also form/structure when translating religious texts (Butnariu, 2017).…”
Section: Translation and Da'wahsupporting
confidence: 65%